New substitute name for the genus Napo Shaw, 2012 (Hymenoptera: Braconidae: Euphorinae) - Zhang, Dao-Wei; Chen, Jing (Zootaxa, 2015)
The braconid genus Napo was established by Shaw (2012) for a single species Napo townsendi Shaw, 2012 from Napo Province, Ecuador. However, the genus name Napo is preoccupied and was initially introduced by Linnavuori & DeLong (1976) for a deltocephalinae leafhopper genus with Napo brazosellus Linnavuori & DeLong, 1976 as the type species (Hemiptera: Cicadellidae). Thus, the genus Napo Shaw, 2012 is a junior homonym of the genus Napo Linnavuori & DeLong, 1976. According to Article 60 of the ICZN (2015), we propose the new replacement name Yanayacu nom. nov. for Napo Shaw, 2012. The resulting nomenclatural changes are summarized below.